SISTEM INFORMASI EMPLOYEE SELF SERVICES DEPARTEMEN HRD-GA PADA PT CENTURY BATTERIES INDONESIA JAKARTA - Ciptadi Nugroho; Petrus Dwi Ananto (METHODIKA: Jurnal Teknik Informatika dan Sistem Informasi, 2017)
Information system technology becomes one of the keys to the success of a company, through its ability to integrate functions in the organization of the company into an effective and efficient work unity. Each department within the organization will attempt to improve on cost and process efficiency. One of the departments within the company's organization in PT Century Batteries Indonesia is Human Resources Development-General Affair and Industrial Relations (HRD / GA) related to the management of all human resources in the company and facilities supporting office activities in the company. In terms of human resource management and general affairs, there are several processes involving employees as objects and subjects in the process. For example, the payroll process, the use of leave facilities and the use of health facilities. Employee involvement will impact on the efficiency and effectiveness of the process, for both the employee and the employee in the HRD / GA department. There are some problems in the HRD / GA department in PT Century Batteries Indonesia, among others, the length of time required in the service of the cover letter of medical treatment, information on leave and payroll information; high operational costs in paper use; and the inability of the HRD / GA department to provide services to employees at all times. Through the prototype method then created an Employee Self Services (ESS) application using a touch screen monitor facility that is able to work automatically to meet the needs of employees in terms of making a cover letter treatment, submission of leave until the provision of employee salary information. The result is that the Employee Self Services application was able to speed up the service process in terms of making the introduction letter for medical treatment, salary and leave information without having to wait for the presence of HRD-GA staff in his office; and able to reduce the cost of paperless operations.